2015
DOI: 10.11591/.v4i3.4728
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Hypertension in Students of Jahangirnagar University: Alarming Issues

Abstract: The prevalence of obesity and hypertension (HTN) in university students of Bangladesh has not reported yet. Considering the proper health maintenance of this population in mind, the study was aimed to determine the prevalence of obesity and HTN as well as relationship among them in the students of a residential university of Bangladesh, Jahangirnagar University. This descriptive cross sectional study included 500 randomly selected students (250 males and 250 females). Participants completed a questionnaire on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…In the present study, males had a 2‐fold higher hypertension prevalence than females (12.2% vs. 6.1%). A higher level of hypertension prevalence has also been found among university male students (9.2% vs. 2%) in a previous study conducted in the Dhaka region 32 . Another study reported a similar finding for hypertension prevalence among medical students (12.1% vs. 3.4%), in the Dhaka region of Bangladesh 13 .…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In the present study, males had a 2‐fold higher hypertension prevalence than females (12.2% vs. 6.1%). A higher level of hypertension prevalence has also been found among university male students (9.2% vs. 2%) in a previous study conducted in the Dhaka region 32 . Another study reported a similar finding for hypertension prevalence among medical students (12.1% vs. 3.4%), in the Dhaka region of Bangladesh 13 .…”
Section: Discussionsupporting
confidence: 70%
“…A higher level of hypertension prevalence has also been found among university male students (9.2% vs. 2%) in a previous study conducted in the Dhaka region. 32 Another study reported a similar finding for hypertension prevalence among medical students (12.1% vs. 3.4%), in the Dhaka region of Bangladesh. 13 In Saudi Arabia, a higher prevalence of hypertension was also found among male (18.5%) students than in female (5.3%) students.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Excess body weight may account for up to 26% of cases of hypertension in men and 28% in women 28. Hypertension rate was 11.1% in our study while 11.2% of the university students were suffering from hypertension in Sudip Paul’s study 12. Weight loss in obese subjects is associated with a decline in blood pressure.…”
Section: Discussionmentioning
confidence: 42%
“…Consequently, obesity is increasing in the Kingdom at an alarming rate 11. Sudip Paul12 conducted an obesity study on university students of Bangladesh. He has reported 25% overweight that is almost similar to our findings (21.7%) but rate of obesity (4%) in his study is significantly less our findings (8.4%).…”
Section: Discussionmentioning
confidence: 99%